Design as a form of culture - O.O. Chernykh (Academy of Cognitive and Natural Sciences, 2007)
In the article the point main of research is one of the aspects of design theory. The author speculates on the evolutionary process of various design forms in the context of Culture Study. The contents of this publication can be used for theory training of future designers.